História evolutiva de duas espécies simpátricas de Furnariidae (Aves: Passeriformes) associadas a diferentes habitats ao longo das várzeas amazônicas - Barbosa, Waleska (Instituto Nacional de Pesquisas da Amazônia - INPA, 2021)
Differentiated habitat use can predict the diversity and genetic structure of Amazonian birds. Making this link between the intrinsic characteristics of organisms and the patterns of genetic diversity can provide us with insights into the evolutionary processes that act on species and also on the history of environments. About 15% of non-aquatic birds in the Amazon are restricted to river-created habitats, and have different levels of habitat affinity. In this study we investigated the evolutionary history of Synallaxis albigularis and Mazaria propinqua, two morphologically very similar species, which occur in the initial successional vegetation along the floodplains in western and central Amazonia, co-occurring along the Solimões River. Although sympatric, they are not syntopic, M. propinqua occurs predominantly in river islands of white water rivers, while S. albigularis occurs along alluvial plains on the river banks, using more diverse types of habitat. We used occurrence data from the museum collections and public databases, and generated genomic data (UCEs, SNPs, and mtDNA) for 49 samples of the two species. Our results showed that the two species present different ages of diversification and population history, and that the different use of the habitat can explain the incongruous patterns found. More ephemeral habitats can produce a higher rate of extinction, producing the bottleneck effect, consequently the populations associated with these environments have low genetic variability, with very recent diversification dates, little structure and smaller population size. More resilient habits show the opposite. In addition, climatic variations in the late Pleistocene and Holocene produced changes in the different types of environments in the Amazonian floodplains that affected the connectivity and the size of the bird populations associated with these environments.
Keywords: História demográfica; habitats alagáveis